Lysophosphatidic Acid Signaling in Late Cleavage and Blastocyst Stage Bovine Embryos. (14th April 2014) - Torres, Ana Catarina; Boruszewska, Dorota; Batista, Mariana; Kowalczyk-Zieba, Ilona; Diniz, Patricia; Sinderewicz, Emilia; Saulnier-Blache, Jean Sebastian; Woclawek-Potocka, Izabela; Lopes-da-Costa, Luis
Abstract : Lysophosphatidic acid (LPA) is a known cell signaling lipid mediator in reproductive tissues. In the cow, LPA is involved in luteal and early pregnancy maintenance. Here, we evaluated the presence and role of LPA in bovine early embryonic development. In relevant aspects, bovine embryos reflect more closely the scenario occurring in human embryos than the mouse model. Transcription of mRNA and protein expression of enzymes involved in LPA synthesis (ATX and c PLA2 ) and of LPA receptors (LPAR1–4) were detected in Days 5 and 8 in vitro produced embryos. Embryonic LPA production into culture medium was also detected at both stages of development. Supplementation of culture medium with LPA (10 −5 M) between Days 2 and 8 had no effect on embryo yield and quality and on blastocyst relative mRNA abundance of genes involved in prostaglandin synthesis ( PTGS2, PGES, and PGFS ) and steroidogenesis (3 β HSD ). However, LPA treatment affected transcription levels of embryo quality markers, decreasing BAX (apoptotic) and increasing BCL2 (antiapoptotic) and IGF2R (growth marker) gene transcription levels. Blastocyst transcription of OCT4 (pluripotency marker) was not affected by LPA stimulation. In conclusion, LPA is an early bovine embryonic autocrine/paracrine signaling mediator, and LPA action may be relevant in early embryo-maternal interactions leading to embryonic survival.